2014
DOI: 10.1007/s11010-014-2229-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and antioxidative responses to endogenous polyunsaturated fatty acid accumulation in yeast

Abstract: Pathophysiology of polyunsaturated fatty acids (PUFAs) is associated with aberrant lipid and oxygen metabolism. In particular, under oxidative stress, PUFAs are prone to autocatalytic degradation via peroxidation, leading to formation of reactive aldehydes with numerous potentially harmful effects. However, the pathological and compensatory mechanisms induced by lipid peroxidation are very complex and not sufficiently understood. In our study, we have used yeast capable of endogenous PUFA synthesis in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 66 publications
(82 reference statements)
3
14
0
Order By: Relevance
“…This effect would enhance biomass yield, but not fermentative capacity, which agrees with our results. Moreover, it has been found that accumulation of fatty acids allows an adaptation to the endogenous oxidative stress associated with higher levels of reduced glutathione 38 , which is also consistent with our results. Finally, caffeic acid has been linked with apoptosis and anticancer and antifungal activities 16 and, at low doses, diminishes lipid peroxidation and blocks ROS due to activation of the cell wall integrity (CWI) pathway 39 40 and GSH homeostasis regulation 41 .…”
Section: Discussionsupporting
confidence: 93%
“…This effect would enhance biomass yield, but not fermentative capacity, which agrees with our results. Moreover, it has been found that accumulation of fatty acids allows an adaptation to the endogenous oxidative stress associated with higher levels of reduced glutathione 38 , which is also consistent with our results. Finally, caffeic acid has been linked with apoptosis and anticancer and antifungal activities 16 and, at low doses, diminishes lipid peroxidation and blocks ROS due to activation of the cell wall integrity (CWI) pathway 39 40 and GSH homeostasis regulation 41 .…”
Section: Discussionsupporting
confidence: 93%
“…PUFAs (stearidonic acid, eicosapentaenoic acid, and docosapentaenoic acid) are major components of the cell membrane of C. parapsilosis, accounting for approximately 30% of the fatty acid content, and have a remarkable antioxidant effect (17). Tyrosol-induced inhibition of the expression of FAD2 and FAD3 found in this study therefore decreases the antioxidant level in cell membranes, which may contribute to the antifungal effect of tyrosol against C. albicans or C. parapsilosis (16)(17)(18). Although tyrosol was reported to exert an antioxidant effect, this was measured only at micromolar concentrations (19), while the concentration used in this study was 15 mM.…”
Section: Discussionmentioning
confidence: 71%
“…As effects of this process, a diversity of reactive aldehydes arises and these aldehydes play an important role in human metabolism. 4-HNE, as one of the reactive aldehydes, influences cellular response to stress, causing an increase in antioxidant enzyme activity, such as catalase [52, 53]. Regarding the data obtained by Andrisic et al .…”
Section: Discussionmentioning
confidence: 99%